Malay Culture Effect on Career Planning Student SMA City 9 Bengkulu - Heni Sulusyawati; Juwanto Juwanto (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2020)
This research is motivated by the discovery of Malay culture students who have not thought of a clear career plan after graduating from high school, Malay culture students are also found to be confused in choosing majors in Higher Education. The purpose of this study was to determine the effect of Malay culture on student career planning. This type of research is a qualitative descriptive study with a natural setting approach. Data collection in this study using observation techniques, interviews, carried out simultaneously with data analysis. Data analysis using the Spradley model, namely through 4 stages of data analysis including domain analysis, taxonomic analysis, componential analysis, and discovering cultural themes. Based on the results of data analysis, it can be explained the influence of Malay culture on student career planning, namely: 1) discipline; students culture Malay discipline in completing the tasks of the teacher, 2) responsibilities; Malay cultural students have a high sense of responsibility in doing assignments, 3) light-handed; Malay cultural students have a mild attitude in mobilizing things that support learning activities, 4) high learning desires; Malay cultural students have a high desire in learning activities both at school and at home, 5) diligent; Malay cultural students are also classified as students who are diligent, it shows students in working on creative tasks.